PENGARUH MODEL TEAM ASSISTED INDIVIDUALIZATION TERHADAP HASIL BELAJAR SISWA DALAM PEMELAJARAN TEMATIK SEKOLAH DASAR - Yola Anggraini; Siti Halidjah; Rio Pranata (Universitas Tanjungpura, 2021)
AbstractThe study aims to analyze the effect of the Team Assisted Individualization model onstudent learning outcomes in thematic learning in class IV SDN 21 Pontianak Timur.The method used is the experimental method, with the form of research non equivalentcontrol group design. The population in this study amounted to 52 grade IV studentsconsisting of 2 classes. The sample was taken by using the non probability samplingteachnique, the type of purposive sampling, which amounted to 52 students. The datacollection technique used is a measurement teachnique using an essay test tool. Theresults showed that the control class pre-test avarage was 45,09 and the experimentalclass was 45.61. The control class post-test was 49.19. Obtained an average of 46.63.Based on the hypothesis test analysis, it was found that there was a difference in thepost-test scores of students between the control class and the experimental class.Obtained the effect size value is 0.63. So the conclusion from the calculation of the effectsize on the application of the assisted individualization team learning model in thematiclearning in learning outcomes has a moderate effect on the fourth grade students ofSDN 21 Pontianak Timur.Keywords: Influence, Learning Outcomes, Team Assisted Individualization Model.